Farm size, farmers' perceptions and chemical fertilizer overuse in grain production: Evidence from maize farmers in northern China. (1st January 2023) - Yu, Xiaomin; Schweikert, Karsten; Li, Yajuan; Ma, Ji; Doluschitz, Reiner
Abstract: China's agriculture is characterized by small-scale farms whose overuse of chemical fertilizers is widespread. This makes it a key challenge for China to sustainably feed its growing population. In this study, we investigate the role of farm size in maize production and how it relates to farmers' fertilizer application strategies. We use cross-sectional survey data of 774 maize-producing farms in northern China, and develop a conceptual framework that links farm production, on-farm resources, the socio-economic characteristics of the households and farmers' knowledge and perceptions as a whole. We use linear and logistic regression models to show that despite the recent declines in fertilizer application rates, excessive fertilizer use persists in maize cultivation in northern China. Farm size has a negative effect on chemical fertilizer use and a positive effect on maize yield. In addition, farmers on large farms achieve significantly higher knowledge scores in terms of fertilizer use and maize cultivation. They are also more likely to attend agricultural training and adopt scientific fertilizer use techniques. Increased farm size, participation in training, better farming knowledge, and having a family member as a village cadre are associated with farmers' decisions to reduce the use of conventional fertilizers. The key to achieving more sustainable grain production in China is to increase farm size, while enhancing the effectiveness of agricultural extension and promoting scientific fertilization techniques. Social networks within and between villages should also be utilized for knowledge transfer. In addition, cooperation between research institutions and fertilizer companies should be further emphasized to improve the accessibility of regionally adjusted formulated fertilizers. Highlights: Excessive fertilizer use persists in maize production in northern China. A conceptual framework linking natural and socioeconomic aspects of maize farms is developed. Increasing farm size has a negative (positive) effect on fertilizer use (maize yield). Smallholder farmers on average have less farming knowledge. Training has the greatest impact on farmers' decision to reduce fertilizer use.